Late Pleistocene lithic technology in the Ivane valley: A view from the rainforest. (20th August 2017) - Ford, Anne
Abstract: Lithic assemblages in late Pleistocene sites within rainforest environments in Southeast Asia and Australasia are characterised as being simple core-and-flake technologies with little evidence for formal tools. This is usually attributed to the Bamboo Hypothesis, which proposes that modern humans first moving into these rainforest environments would have exploited available plant resources such as wood or bamboo at the expense of lithic technology. This paper challenges this portrayal by reporting the presence of formal tools in the Ivane valley of Papua New Guinea, dating from first occupation between 43, 000–49, 000 years cal BP.